Identifikasi Anak dengan Gangguan Psikologis Akibat Bullying pada Siswa Sekolah Dasar: Strategi Dampak dan Intervensi - Zulvia Misykah; Nur Wahyuni; Dewi Sartika Panggabean; Dinda Widyastija (STKIP Taman Siswa Bima, 2023)
Research on the identification of children experiencing psychological disorders due to bullying in elementary school students is important because it can help identify and address mental health problems that often go undetected in children who experience bullying, and can provide a basis for the development of effective intervention programs to prevent and address the impact worse than bullying in children. The aim of the research is to identify psychological symptoms that appear in children who are victims of bullying, evaluate the long-term impact of bullying on children's mental health, and design appropriate intervention strategies to help children who experience psychological disorders due to bullying. The research method uses a quantitative and qualitative approach. The selected population is all elementary school students who experience bullying, while the selected sample is a small portion of the population which is represented by children who have experienced psychological symptoms due to bullying. Data analysis techniques that can be used are descriptive analysis to analyze quantitative data, and thematic analysis to analyze qualitative data. The results of research on identifying children who experience psychological disorders due to bullying in elementary school students show that children who are victims of bullying have a higher risk of experiencing psychological symptoms such as depression, anxiety, fear, social isolation, and other behavioral problems. The long-term effects of bullying on a child's mental health include lowered self-esteem, decreased academic achievement, difficulties in building interpersonal relationships, and a higher risk of developing mental health disorders in the future